PENGARUH VARIASI KOMUNIKASI LIVE ASMR TERHADAP KUALITAS ISTIRAHAT GENERASI Z - Mochamad Varrel (Sintesa, 2026)
This study examines the effect of communication pattern variation in live ASMR on the relaxation level and rest quality of Gen Z. ASMR is understood as an audio-visual stimulus that may evoke comfort and calm through whispering, soft intonation, personal attention, and real-time interaction. The study employed an explanatory quantitative design with purposive sampling involving 200 Gen Z respondents who had watched live ASMR on TikTok. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability tests, classical assumption tests, and linear regression. The results show that communication pattern variation has a positive and significant effect on relaxation, and relaxation has a positive and significant effect on rest quality. In addition, personal attention, soft intonation, and whispering were identified as the most effective communication patterns in creating audience comfort. These findings indicate that live ASMR can serve as a relevant digital relaxation medium for Gen Z and may support better rest. Keywords: Live ASMR, Communication Patterns, Relaxation, Rest Quality, Gen Z